2018
DOI: 10.1073/pnas.1810555115
|View full text |Cite
|
Sign up to set email alerts
|

HflXr, a homolog of a ribosome-splitting factor, mediates antibiotic resistance

Abstract: SignificanceAntibiotics have been widely used to treat bacterial infections and are also found in the environment. Bacteria have evolved various resistance mechanisms, allowing them to overcome antibiotic exposure and raising important health issues. Here, we report a bacterial antibiotic resistance mechanism, based on ribosome splitting and recycling, ensuring efficient translation even in presence of lincomycin and erythromycin, two antibiotics that block protein synthesis. This mechanism is mediated by a Hf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 37 publications
4
67
0
Order By: Relevance
“…7), demonstrating that the ribosome-associated HrpA and SCO2532 proteins indeed contribute to resistance to translation-targeting antibiotics. Interestingly, the strain lacking HflX ribosomeassociated GTPase showed a significant effect on sensitivity to erythromycin (fourfold), supporting a previous report that a hflX homolog mediates erythromycin resistance (47,48). Complementation of the hrpA, SCO2532, or hflX gene restored resistance to erythromycin or tetracycline (except SCO2532 to tetracycline sensitivity), further supporting that these proteins directly mediate antibiotic resistance.…”
Section: Category (No Of Genes) Asupporting
confidence: 81%
“…7), demonstrating that the ribosome-associated HrpA and SCO2532 proteins indeed contribute to resistance to translation-targeting antibiotics. Interestingly, the strain lacking HflX ribosomeassociated GTPase showed a significant effect on sensitivity to erythromycin (fourfold), supporting a previous report that a hflX homolog mediates erythromycin resistance (47,48). Complementation of the hrpA, SCO2532, or hflX gene restored resistance to erythromycin or tetracycline (except SCO2532 to tetracycline sensitivity), further supporting that these proteins directly mediate antibiotic resistance.…”
Section: Category (No Of Genes) Asupporting
confidence: 81%
“…Both classes of proteins show homology to the translation factors, EF-G and EF-Tu, and actively trigger the release of the antibiotic bound to the ribosome (14,(36)(37)(38)(39). Dissociation of ribosomes stalled in the presence of antibiotics and rescue of mRNA has, however, not been described as a mechanism of antibiotic resistance until very recently, when Duval et al (29) demonstrated that deletion of Listeria monocytogenes hflX-r (lmo0762) confers sensitivity to erythromycin and lincomycin and results in accumulation of 70S ribosomes in the mutant strain on antibiotic exposure. Interestingly, L. monocytogenes encodes 2 HflX paralogs, only 1 of which is involved in antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although binding of macrolides has been shown to interfere with the GTPase activity of E. coli HflX, the E. coli HflX has not been shown to be directly involved in antibiotic resistance (28). Recently, the hflX-r gene from Listeria monocytogenes was shown to confer macrolide resistance (29). We demonstrate here that Mab-HflX (MAB_3042c) and Ms-HflX (MSMEG_2736) are required for macrolide-lincosamide resistance in M. abscessus and M. smegmatis, conferring equivalent resistance as the erm genes, by an erm-independent pathway.…”
Section: Significancementioning
confidence: 99%
“…We note that a few of the predicted core gene alleles are of genes previously associated to resistance against the corresponding antibiotic, if not necessarily in the target organism or mechanistically established. For instance, an HflX-like protein is known to confer resistance in erythromycin in Listeria monocytogenes through ribosome recycling [52], and it is possible that the hflX gene discovered here may similarly confer resistance in S. aureus. In Helicobacter pylori, oppD was found to be significantly induced by gentamicin exposure [53].…”
Section: Characterization Of Candidate Novel Amr Genesmentioning
confidence: 97%